PEMBUATAN HAND SANITIZER ALAMI DI DESA CEMPAKA BARU KOTA BANJARBARU - Noer Komari; Dwi Rasy Mujiyanti; Dewi Umaningrum; Dahlena Ariyani (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2021)
The spread of Covid-19 was out of control and spread throughout Indonesia, including Banjarbaru which had a red zone. Desa Cempaka Baru Kota Banjarbaru is a transmigration settlement that is still safe against Covid-19. Even though it is safe, the community is quite at high risk of contracting it. People are required to comply with health protocols, especially cleaning their hands, including using a hand sanitizer. The demand for hand sanitizers in the market is increasing and the price is also rising, so an alternative is needed to make your own hand sanitizer. The aim of the activity is to educate village communities to make hand sanitizers by utilizing materials around their environment. The activity stages include socialization, implementation of making hand sanitizers, and evaluation. Assistance in the form of hand sanitizer products, hand washing stations, and banners advising the prevention of Covid-19 transmission were also provided to the public. The process of making hand sanitizers was demonstrated by students who helped with activities and involved 15 women who were members of the “Sasirangan Working Group”. The service product is a natural hand sanitizer made from lemongrass and betel leaves. The community was very enthusiastic about participating in this activity and promised to make their own later.